Effect of Alkaline-Acid Treatment on the Biomimetic Formation of Calcium Phosphate Layers on Titanium Substrates: An In Vitro Study: Alkaline-acid treatment on calcium phosphate layers - Aliasghar Behnamghader; Hoda Salemi; Abdollah Afshar; Mahmood Ardeshir (Iranian Journal of Pharmaceutical Sciences, 2008)
The aim of this study was to investigate the effect of alkaline and heat treatment and acid etching of titanium substrates on the formation of calcium phosphate layer and bioactivity in simulated body fluid (SBF) solution. In this research, at first the titanium surfaces were treated with 5N NaOH, 15% HNO3-10%HF-75% H2O and 5N NaOH followed by heating at 600 ºC for 1h. The samples were immersed in the SBF for 28 days to investigate the influence of surface treatments of titanium on in vitro bioactivity. The modified substrates were characterized using scanning electron microscopy, X-ray diffraction and profilometry of samples were investigated by light interferometry. The in vitro assessment was carried out through the immersion of samples in SBF. According to the results obtained in this work the deposit of calcium phosphate in alkali and alkali/heat treated samples were more stable than acid etched samples. Porous network structure containing the sodium titanate and the titanium oxide was characterized on the surface after the titanium was subjected to NaOH aqueous solution. Results have illustrated the fact that chemical surface treatment improves in vitro behavior of titanium.